Governance Dalam Perspektif Auditor Internal Dan Pengaruhnya Terhadap Kemungkinan Kebangkrutan Perusahaan - Hotman Fredy; Salis Musta Ani (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2014)
This study examines the effect of the application of appropriate corporate governance guidelines for the internal auditor to the possibility of companies experiencing financial difficulties. Together with the control variables, ieLeverage, ROA, Quick Ratio, EPS, and Size, conducted testing using Binary Logit with the dependent variable. Panel data of 25 companies listed on the Indonesia Stock Exchange (BEI) for the total of 50 firm year traced through the annual report, IDX websites and corporate websites, as well as ICMD.The results show that Leverage and Size significantly influence the likelihood companies experiencing financial difficulties. However, this study failed to prove that the company's corporate governance affects the possibility of experiencing financial difficulties. Nevertheless, obtained a description of the application of corporate governance as defined by the guidelines of the internal auditors on average 79%. This proves that the internal auditor is also one of the governance that have contributed to the implementation of good corporate governance in the company so that it can be used as representation of the CG with other CG mechanisms.